Estancias, poblados fundadores - Güiraldes, Juan José (1997)
Historia y evocación de la Estancia de la llanura pampeana
Keywords: ESTANCIAS; ARGENTINA; SIGLO XIX; POBLADOS; URBANISMO; HISTORIA; VIVIENDAS RURALES